Czynniki destabilizacji politycznej w Karaczajo-Czerkiesji: separatyzm etniczny i fundamentalizm religijny - Sieradzan, Przemysław J. (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2012)
The Republic of Karachay-Cherkessia is among the most unstable entities of the Russian federation. Whereas the ideas of radical political Islam enjoy little popularity there, the ethnic structure is exceptionally complex, which is not reflected in the model of territorial administration. The scale of corruption and nepotism of the local elite is enormous. The relations between the two titular ethnicities of Karachay-Cherkessia abound in mutual prejudices and distrust, or even hostility. The current model of a two-nationality republic is an element of the Soviet legacy, originally introduced in order to overcome ethnic particularism. The decline of the Soviet model of state fostered ethnic particularism and separatism, which applied to Karachays and Cherkessians alike at the turn of the nineteen-eighties. At present, Karachay separatism is a marginal phenomenon, while the influence of the Pan-Cherkessian movement has been consistently growing, posing an increasing threat to the territorial integrity of the Russian Federation. The author characterizes various dimensions of ethnic separatism in Karachay-Cherkessia and analyzes the reasons for the weakness of the armed Islamist underground in this Caucasian republic.
The factors of political destabilization in Karachay-Cherkessia: ethnic separatism and religious fundamentalism